Transport economics - Stubbs, P. C.; Tyson, W. J.; Dalvi, Quasim (London ; Boston : G. Allen & Unwin, 1980)
This book explore the economics of transportation.
Includes index.
Bibliography: p. 205-213.
ijb, 15/01/2019
Loans
Keywords: Transportation; Transport economics; Great Britain